ABO blood group and thrombotic vascular disease - Franchini, Massimo; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 2014)
ABO blood group antigens are complex carbohydrate molecules expressed on red blood cells and a variety of tissues. The ABO blood type is implicated in the development of a number of human diseases and there is increasing evidence regarding its involvement in the pathogenesis of cardiovascular disorders, mainly through its effect on von Willebrand factor levels. In this review, after a brief analysis of the potential molecular mechanisms by which the blood group influences haemostasis, we focus on the clinical implications of such interaction. Overall, the literature data document the close relationship between venous thromboembolism (VTE) and non-O blood type, which is associated with an approximately two-fold increased risk of venous thrombosis. A supra-additive effect on VTE risk is observed when an inherited thrombophilic condition is associated with non-O blood group. A weaker association exists between non-O blood type and arterial thrombosis, which needs to be further investigated.
Keywords: ABO blood group; thrombosis; venous thromboembolism; arterial thrombosis; coronary heart disease